Simultaneous removal of organic carbon, nitrogen, and phosphorus from a domestic wastewater using anaerobic sequencing batch reactors - Fongsatitkul, P.; Elefsiniotis, P.; Yoosook, S.; Karcharnubarn, R. (Malaysian Journal of Science, 2004)
This research demonstrated the feasibility of using anaerobic sequencing batch reactors (An A2/02 SBR) to achieve simultaneous removal of organic carbon, nitrogen, and phosphorus from a domestic wastewater. The effects of influent carbon to nitrogen (C/N) ratio, solids retention time (SRT), and maximum system loading capacity on process performance were investigated. It was found that a minimum influent chemical oxygen demand (COD) concentration of 300 mg/L and a corresponding COD to total Kjeldahl nitrogen (COD/TKN) ratio of 7 were required in order to obtain a satisfactory (over 90%) phosphorus removal level. Since the wastewater used was deficient in carbon, addition of glucose as an external carbon source was necessary to maintain the above influent COD/TKN ratio. Furthermore, the percent total phosphorus (TP) removal can be correlated either to the influent COD concentration or to the COD/TKN ratio in a quantitative manner using polynomial expressions. An increase in SRT from 20 to 30 days did not affect COD performance; however, it improved remarkably both TKN and TP removal elTiciencies. On the other hand, an increase in the organic loading rate to a level of 0.63-0.66 kg COD/m3-d or higher appeared to reduce significantly the ability of the system regarding the phosphorus removal, and to a lesser extent the nitrogen removal efficiency.